Strategy and Management of Preaching (Da’wah) Development of Indonesian Islamic Da'wah Institute Since 1990 Until 2017 - Umam, Hoerul (UIN Sunan Gunung Djati Bandung, 2018)
The Indonesian Islamic Da'wah Institute (LDII) is connoted as the successor of the Islamic struggle of the Jamaah, so that a false labeling emerges by certain parties. Although there are many indications that direct such perceptions, LDII is essentially an organization formed by the New Order government that is tasked with fixing the deviations of Islamic teachings by the Islamic Jamaah group. From 1990 to 2017. The strategy and management of the development of the propaganda of the Indonesian Islamic Propagation Institute from 1990 to 2017 further enhances religious understanding of its members. Although the number of worshipers can increase but that is the focus of his preaching on the improvement of religious understanding. In carrying out its religious activities, members or worshipers do not have to be fixated on their place of residence. But LDII members can attend the study at the LDII mosque on the spot. Management in this LDII Organization in carrying out its Islamic da'wah is accompanied by plans, work programs and evaluation of the activity process. And it is personal by inviting the closest Muslim community such as relatives, neighbors to participate in its activities. LDII uses strategies in the fields of religion, sports and others to develop its Islamic da'wah.